Adolescent Prayer Mentoring as a Technology for Spiritual Human Capital Formation - Anisa, Lina Nur; Tyas, Zuhriana Widya Rahayu Ning (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study conceptualizes adolescent prayer mentoring as a structured pedagogical technology for spiritual human capital formation and examines its relevance for psychosocial and non-military resilience. Methodologically, it employs qualitative library research with a normative-conceptual orientation supported by a Systematic Literature Review (SLR). Data were collected from peer-reviewed journal articles, academic books, and institutional reports on adolescent spirituality, Islamic pedagogy, prayer practices, character formation, spiritual capital, human capital, psychosocial resilience, and non-military resilience. Literature was traced through Scopus Preview, DOAJ, and Google Scholar using keywords such as “adolescent prayer mentoring,” “Islamic pedagogy,” “religious pedagogy,” “spiritual human capital,” “self-regulation,” “meaning-making,” “social empathy,” and “non-military resilience.” The initial search identified more than 120 sources. After screening for relevance, conceptual clarity, and contribution to the proposed framework, 47 studies were retained, and 32 core sources were selected for synthesis. Data analysis followed the SLR stages of identification, screening, selection, classification, and conceptual synthesis. The selected literature was organized into four analytical themes: prayer as Islamic pedagogical formation, prayer mentoring and value internalization, spirituality–psychosocial resilience–character formation, and spiritual human capital–non-military resilience. Findings show that prayer mentoring operates through bodily and spiritual habituation, reflective dialogue, moral exemplarity, emotional regulation, autonomous value internalization, meaning in life, and social empathy. These mechanisms transform prayer from private ritual observance into spiritual human capital for sustainable, resilient civic life. The article proposes the pathway: prayer mentoring → self-regulation → meaning in life → social empathy → spiritual human capital → non-military resilience.